Improvements to the EPA Industrial Source Complex Dispersion Model - Atkinson, Dennis G.; Bailey, Desmond T.; Irwin, John S.; Touma, Jawad S. (Journal of applied meteorology (1988), 1997)
Air quality models are a key component in determining air pollution control requirements. The Industrial Source Complex (ISC2) model is a steady-state Gaussian plume model that is used for modeling point, area, volume, and line sources. Since its development in the 1970s by the U.S. Environmental Protection Agency, this widely used model has undergone several updates as state-of-the-science techniques have become available. Some of the recent modifications to the ISC2 model include a numerically efficient area-source algorithm tested in wind tunnel experiments, a dry-deposition algorithm that can account for a full range of particle size distributions, an algorithm for calculating wet-deposition flux using the scavenging coefficient approach, and an algorithm for modeling open-pit sources. These modifications, which are part of the current ISCST3 model, are described in detail within this paper. In addition, a plume depletion model demonstration was performed to compare observed and estimated crosswind integrated concentrations of a depositing tracer as functions of travel time and stability.